Ethical-methodological reflections of the research on sexual and gender dissidence in a university context - Acuña Rodríguez, María del Carmen (2021)
The paper addresses methodological and ethical issues for research about sexual and gender diversity, based on reflections built by the author as a result of the studies developed in that subject (having the University of Costa Rica as the studies’ context). From an intercultural perspective, ruptures and resignifications for the forms of doing research are proposed. There are shared several reflections concerning: the type of study, the research’s participants (students, teachers and administrative staff, who self-identify as LGBTIQ+), the dialogue as a methodological strategy, the use of metaphors to reflect realities, and the researcher’s experience among the investigative processes. The last aspect in terms of the researcher’s personal position of the, the development stages of the studies, and the emotions involved. Finally, an invitation is given to rethink the traditional practices of generating science.